The Power of Two Learning Strategy in Islamic Religious Education Material Shaping Character Student - Masturin, Masturin (Nazhruna: Jurnal Pendidikan Islam, 2024)
The power of two learning strategies in Islamic Religious Education (PAI) has been studied to assess its effectiveness in shaping students' character. This research aimed to investigate the implementation of this strategy in PAI material and its impact on character building. A qualitative case study approach was employed, involving school principals, students, and PAI teachers from senior high schools in Kudus City, Central Java, Indonesia, as informants selected through purposive sampling. Data were collected through in-depth interviews, participant observation, documentation, and focus group discussions. Validity was ensured through extended researcher presence, triangulation, peer discussion, transferability, dependability, and confirmability measures. The research findings revealed that the power of two learning strategies in PAI material could effectively and efficiently shape students' character by creating synergy between teachers and students in the learning process. This research contributes to the theoretical and practical development of PAI learning materials for character education, providing insights for the government in implementing such strategies in the curriculum.